The Hubungan penggunaan media sosial dengan kualitas tidur siswa dan siswi SMA 21 Makassar - Syamsuriyati Syamsuriyati; Rika Handayani (Jurnal Ilmu Kebidanan, 2023)
The development in the field of science, information and technology is rapidly increasing in this era. People cannot be separated by using the internet, including teenagers. This research was to determine the relationship between the use of social media and the students’ quality of sleep in SMA Negeri 21 Makassar. This study used quantitative research with a cross sectional approach. The population was all students of SMA 21 Makassar and a sample was students of class XII of SMA 21 Makassar. The sampling technique was purposive sampling with a total sample of 75 respondents. This research was conducted in July 2023. The tools used were a social media questionnaire and a PSQI (Pittsburgh Sleep Quality Index) questionnaire. The scale used was the Likert scale with univariate, bivariate and analysis tests. Chi-Square statistics with a significance level of α ꞊ 0.05. There was a significant relationship between the use of social media and the students’ sleep quality in SMA Negeri 21 Makassar with a p-value of ꞊ 0.00. It can be concluded that there is a significant relationship between social media use and sleep quality in students. It is expected that students can control the use of smartphones properly and students are able to manage their sleep schedules.